Differences in the Relative External Load Demands of Pre-Competitive Warm-Ups and Official Matches in Semi-Professional Football Players: A Pilot Study Considering Specific Positions - José María Escudero-Ferrer; Luis Manuel Martínez-Aranda; Manuel Sanz-Matesanz; Konstantinos Spyrou; Pedro E. Alcaraz; Javier Raya-González (Journal of Functional Morphology and Kinesiology, 2025)
Background: A pre-competition warm-up is considered a key strategy for optimising physical preparedness and potentially reducing injury risks in football. Programmes such as FIFA 11+ have demonstrated efficacy in this regard. Its effectiveness depends on alignment with match demands. This study compares the relative external load demands of warm-ups and matches in semi-professional football players, focusing on positional differences. Objective: The goal of this study was to evaluate whether warm-ups adequately prepare players for match demands and to explore positional variations. Methods: This is a retrospective study that analysed 19 semi-professional male players during the 2023/2024 season. External load demands (m/min) were measured using a GPS, covering the total distance (TD), speed zones (DZ1–DZ5), accelerations (ACCs), and decelerations (DECs). Paired t-tests and effect size calculations compared team-wide and position-specific demands. Results: Match demands significantly exceeded warm-up demands across all distance-related variables, except for DZ1 (67.06 vs. 66.40 m/min for warm-ups and games, respectively). The greatest differences were observed in TD (80.73 vs. 107.12 m/min; −26.39%) and DZ2–DZ3 (−17.42 and −4.89%, respectively). A positional analysis revealed that concerning DZ1, midfielders covered more distance during competitions (67.62 vs. 65.04 m/min; −2.58%), while full-backs covered more during the pre-competition warm-up (69.01 vs. 66.86 m/min; 2.14%). Additionally, midfielders, wingers, and forwards experienced higher match demands in DECs (1.04; 1.12, and 1.18 nº/min; range = 0.23–3.13%), whereas central defenders showed higher values during the pre-competition warm-up (1.14 nº/min; 0.13%). No significant differences were found for ACCs across any position; however, central defenders showed higher nº ACCs during warm-up (1.04 vs. 0.97 nº/min). Conclusions: These findings enable clubs and coaches to redesign their warm-up protocols to align as closely as possible with the demands of matches, particularly in high-speed zones, to enhance readiness, thereby increasing the effectiveness of warm-ups in football competitions. Additionally, this approach allows for the individualisation of warm-up routines based on the player’s specific position.